2013
DOI: 10.1002/glia.22585
|View full text |Cite
|
Sign up to set email alerts
|

The role of astrocytes in mediating exogenous cell‐based restorative therapy for stroke

Abstract: Astrocytes have not been a major therapeutic target for the treatment of stroke, with most research emphasis on the neuron. Given the essential role that astrocytes play in maintaining physiological function of the central nervous system and the very rapid and sensitive reaction astrocytes have in response to cerebral injury or ischemic insult, we propose to replace the neurocentric view for treatment with a more nuanced astrocytic centered approach. In addition, after decades of effort in attempting to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 233 publications
(319 reference statements)
0
54
0
Order By: Relevance
“…Stroke induces highly dynamic alterations of the neurovascular unit, which contribute to the development of brain injury (9). During stroke recovery, ischemic brain undergoes limited remodeling, with a set of highly interactive processes involving components of the neurovascular unit and neural stem cells (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke induces highly dynamic alterations of the neurovascular unit, which contribute to the development of brain injury (9). During stroke recovery, ischemic brain undergoes limited remodeling, with a set of highly interactive processes involving components of the neurovascular unit and neural stem cells (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the very initial work on neurorestorative therapy for the treatment of neural injury and disease was performed using cell-based therapy. Stem/progenitor cells stimulate a set of highly interactive processes, such as angiogenesis, neurogenesis, oligodendrogenesis, synaptogenesis and axonal outgrowth, which in-concert orchestrate neurological recovery [3,4]. Cell-based therapy, for example, stimulates the generation of angiogenic factors that promote vascular remodeling, and the activated and newly formed endothelial cells act as a source of trophic factors, that also enhance neurogenesis within the subventricular zone (SVZ) and neurite outgrowth.…”
mentioning
confidence: 99%
“…Cell-based therapy, for example, stimulates the generation of angiogenic factors that promote vascular remodeling, and the activated and newly formed endothelial cells act as a source of trophic factors, that also enhance neurogenesis within the subventricular zone (SVZ) and neurite outgrowth. The newly formed cells migrate from the SVZ to the region of injury, interact with activated vasculature and differentiate into neurons and oligodendrocytes (OLGs) [3][4][5]. This restorative tapestry of events creates a supportive environment for neurovascular plasticity, neurite outgrowth and myelination of axons.…”
mentioning
confidence: 99%
“…Astrocyte–endothelial cell interactions have also been shown to be essential in regulating brain water content and electrolyte balance under normal and pathological conditions 48, 49. Ischemic injury to the brain activates astrocytes, and reactive astrocytes can exert a deleterious role (secrete proinflammatory cytokines, inhibit axonal regeneration, infarct expansion) in the acute phase after stroke while exerting a protective role (neurite sprouting, synapse formation, rebuild BBB, secrete neurotrophic factors) in the chronic phase after stroke 50, 51. Using a model of forebrain ischemia in rats, it has been reported that diabetic hyperglycemia suppresses ischemia‐induced astrocyte activation, increases astrocyte cell death, damages the astrocyte end‐foot lining around cerebral vessels, and the damaged astrocytes exhibit increased withdrawal of the astrocyte end‐foot from the cerebral vessel wall 52, 53.…”
Section: Blood–brain Barrier Disruption In Diabetic Strokementioning
confidence: 99%